Participation Level of Continuing Professional Development (CPD) Program Nurses RSI Surabaya - Muhadi Muhadi; Titin Wahyuni (Jurnal Keperawatan, 2021)
Introduction : Nurses are an integral part of patient care and play an important role in improving the quality of care in the hospital. Nurses have a responsibility to ensure patient safety with reliable and guaranteed competence. Nurse competence must be maintained through continuous professional development. Objective : The purpose of this study was to map the level of participation, driving and inhibiting factors for the implementation of the Continuing Professional Development (CPD) program. Method : This study used a cross-sectional study design with a quantitative descriptive approach. The study population was all RSI nurses with a total sample of 104 survey participants with purposive sampling technique. Data were collected using an online questionnaire through the google form application from June to September 2020. Results : The results of the study were the level of participation of nurses at the Surabaya Islamic Hospital in carrying out CPD activities which were divided into 3 categories, namely high, medium and low participation. A total of (17.3%) belonged to the low level of participation, (69.2%) the level of participation was medium and (13.5%) was classified as high. Conclusion : Short-term development plans are a priority for nurses' thinking in improving (CPD), namely the continuous fulfillment of complete nursing care practices and increasing the clinical career level. The long-term development plan for nurses is that some want to continue educational programs at a higher level such as specialized education and master's degree in nursing <w:LsdExcept